Assessment of biogas production and bacterial load from manure of layer chicken fed with two different types of feed. Issue 10 (16th September 2022) - Haque, Mohammad Enamul; Ryndin, Roman; Mang, Heinz‐Peter; Kabir, Humayun; Rahman, Mohummad Muklesur; Khasruzzaman, Abul Kalam Mohammad; Uddin, Mohammad Asir; Islam, Mohammad Alimul
Abstract: Background: The focus of this research was to assess the biogas production of Chicken Manure (CM) collected from hybrid layer chickens fed non‐commercial (CMNC) and commercial (CMC) feed, as well as to evaluate the bacterial load of feeding stock and digested slurry samples before and after Anaerobic Digestion (AD). The effects of the feedstock and digestion composition of CM on biogas production were measured. The experiment was carried out utilizing lab‐based proto‐type digesters for CM with or without inoculum. For each commercial and non‐commercial feed, four experimental groups (CMNC1, CMNC2, CMC1, and CMC2) were designed using mixing ratios of CM: H2 O: inoculum (25:25:50) and CM: H2 O (50:50). For Hydraulic Retention Time (HRT), the digesters were set up at ambient temperature (28–34°C) for 30 days. The spread plate technique was used to determine the Total Viable Count (TVC), E. coli, and Salmonella spp. counts. Results: The highest average cumulative biogas yield was achieved from CMC2 > CMNC2 > CMC1 > CMNC1. The biogas production of inoculum added groups were statistically significant ( p < 0.01 ) than the without inoculum groups. The average concentration of CH4 and CO2 in biogas was 49% and 51% for CMNC1, 58% and 42% for CMNC2, 46% and 54% for CMC1, 52% and 42% for CMC2. However, the H2 S content was within the acceptable range except for the CMNC2 group. The bacterial load was decreased by 2–3 logs before and after AD, and this reduction was statistically significant ( p < 0.05 ). Conclusion: The study concluded that the CM diluted with water and inoculum (25:25:50) ratio was recommended for sustainable biogas production.